Properties of wood plastic composite by using hibiscus cannabinus spp. (kenaf) as a raw material / Mohammad Zahin Khalil - Khalil, Mohammad Zahin (Faculty of Applied Sciences, 2015)
This research is aimed to investigate the mechanical and physical properties of the thermoplastic composite from the kenaf species. The strength were tested for water absorption, thickness swelling, bending (Modulus of Rupture and Modulus of Elasticity), and tensile tests (Stress and Strain) based on ASTM standards. In this study, one paramaters used which was size of particles (150 IJm, 180 IJm, and 250 IJm). From the study, it can be concluded that the smallest size (150 IJm) compare to others particles size (180 IJm and 250 IJm) exhibited the highest strength of wood plastic composite compare to others size.